THE ESTIMATION OF RADIATION GAMMA-BACKGROUND AND CONCENTRATION OF LONG-LIVING TECHNOGENIC RADIONUCLIDES OF137Cs AND90Sr IN SOILS OF CITY-RESORTS OF CAUCASIAN MINERAL WATERS - I. S. Pomelyayko (Известия высших учебных заведений: Геология и разведка, 2017)
The equivalent dose rate of gamma radiation of the resort cities of the Caucasian Mineral Waters (CMW) region has been estimated. During the radiation-ecological monitoring in Zheleznovodsk, anomalies have been found in which the measured values were very different from the rest. For most of the area studied, the dose rates of the gamma radiation have been established to meet the requirements of the sanitary rules and hygienic standards. As a part of the assessment of the ecological state of the urban area, the radio-geochemical studies of the soils of the resorts of the CMW have been carried out, according to which the concentrations of the long-lived technogenic radionuclides137Cs and90Sr have been established. The results of the monitoring indicate that the maximum radionuclide concentrations have been recorded in the soils of Zheleznovodsk, where their average values exceed the corresponding values for Russia by 4 times for137Cs and 13 times for90Sr. The minimum concentrations of137Cs and90Sr are characteristics of the soils of Kislovodsk. According to the content of137Cs and90Sr soils, a dangerous level of the soil contamination is prevailing in Yessentuki, an extremely dangerous one - in Zheleznovodsk, a moderately dangerous one - in Kislovodsk. The obtained results testify that with the environmental assessment of the territory of the CMW region, the application of the evaluation criteria without taking into account the radiation situation can lead to a false conclusion about the magnitude of the anthropotechnogenic load. Based on the information received, a conclusion has been made on the need for further radioecological observations in this region.